2020
DOI: 10.17268/sci.agropecu.2020.02.15
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and other emerging viruses and their relationship to safety in the food chain

Abstract: REVIEW El SARS-CoV-2 y otros virus emergentes y su relación con la inocuidad en la cadena alimentaria SARS-CoV-2 and other emerging viruses and their relationship to safety in the food chain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…They bring together large numbers of people in crowded spaces at considerable risk of contagion [ 142 ]. According to Hasöksüz et al [ 143 ] and Silva-Jaimes [ 144 ], in such traditional food markets where human–wildlife interactions and cross-species infections are frequent, novel coronaviruses are likely to emerge periodically. Petersen et al [ 135 ] also expect a post-COVID-19 pandemic of another coronavirus, an influenza virus, a paramyxovirus, or a completely new disease to be highly likely in the nearest future.…”
Section: Discussionmentioning
confidence: 99%
“…They bring together large numbers of people in crowded spaces at considerable risk of contagion [ 142 ]. According to Hasöksüz et al [ 143 ] and Silva-Jaimes [ 144 ], in such traditional food markets where human–wildlife interactions and cross-species infections are frequent, novel coronaviruses are likely to emerge periodically. Petersen et al [ 135 ] also expect a post-COVID-19 pandemic of another coronavirus, an influenza virus, a paramyxovirus, or a completely new disease to be highly likely in the nearest future.…”
Section: Discussionmentioning
confidence: 99%
“…Chin et al [1] and Van Doremalen et al [2] suggested that SARS-CoV-2 remains viable from 3 h to 7 days, depending on the type of surface. COVID-19 is a disease that probably originated from the increased interaction among wild animals, farm animals and human beings [3]. It has been classified as a pandemic as it is caused by a new influenza-type virus, which has spread worldwide, and most people are not immune to it.…”
Section: Introductionmentioning
confidence: 99%